High-Powered Performance Pay and Crowding Out of Nonmonetary Motives - Huffman, David; Bognanno, Michael (Management Science, 2018)
A previous literature cautions that paying workers for performance might crowd out nonmonetary motives to work hard. Empirical evidence from the field, however, has been based on between-subjects designs that are best suited for detecting crowding out due to low-powered incentives. High-powered incentives in the workplace tend to increase output, but it is unknown whether this masks crowding out. This paper uses a within-subject experimental design and finds evidence that crowding out also extends to high-powered incentives in a real work setting with paid workers. There is individual heterogeneity, however, with a minority of workers reporting crowding in of motivation. Thus, the impact of performance pay might depend on the mix of worker types. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2846 . This paper was accepted by Uri Gneezy, behavioral economics.